Diagnostic and therapeutic management algorithm for biliary complications in living liver donors. (29th September 2021) - Yilmaz, Sezai; Akbulut, Sami; Usta, Sertac; Ozsay, Oguzhan; Sahin, Tevfik Tolga; Sarici, Kemal Baris; Karabulut, Ertugrul; Baskiran, Adil; Gonultas, Fatih; Ozdemir, Fatih; Ersan, Veysel; Isik, Burak; et al.
Summary: This study aimed to demonstrate the efficacy of our diagnostic and therapeutic management algorithm and catheter‐assisted (percutaneous transhepatic biliary tract drainage [PTBD] or transanastomotic feeding tube) hepaticojejunostomy (HJ) procedures in living liver donors (LLDs) with biliary complications. Living donor hepatectomy (LDH) was performed between September 2005 and April 2021 in 2 489 LLDs. Biliary complications developed in 220 LLDs (8.8%), 136 of which were male, and the median age was 29 (interquartile range [IQR]: 12) years. Endoscopic sphincterotomy ± stenting was performed in 132 LLDs, which was unsuccessful in 9 LLDs and required HJ. Overall, 142 LLDs underwent interventional radiologic procedures. Fifteen LLDs with biliary complications underwent HJ (PTBD catheter = 6 and transanastomotic feeding tube = 9) at a median of 44 days (IQR: 82). Following HJ, 14 LLDs did not have any complications throughout the median follow‐up period of 1619 days (IQR: 1454). However, percutaneous dilation for HJ anastomotic stricture was performed in one patient. Biliary complications are very common following LDH; therefore, surgeons in the field should have a low threshold to perform HJ for biliary complications that persist after other treatments. Our catheter‐assisted HJ techniques demonstrated a high success rate and aided HJ in a hostile abdomen during revisional surgery. Abstract : Donor biliary complications are among the most important causes of postoperative morbidity and rarely mortality. However, there is no general consensus on the management of these complications. In this study, we aimed to define a new diagnosis and treatment algorithm donor biliary complications.